The Impact of Digitalization on Manufacturing Firms’ Competitiveness, Environmental Sustainability, and Social Inclusiveness - Abbasi, Rashid Shabir; Saboor, Abdul; Azhar, Auns; Khan, Sajid (Asosiasi Ahli Administrasi Indonesia, 2024)
Manufacturing is a crucial driver of economic growth, contributing approximately 17% to global GDP. This research investigates the impact of digitalization on manufacturing firms' competitiveness, environmental sustainability, and social inclusiveness, using Canon Inc.’s operations globally as a case study. Existing literature underscores the transformative potential of digital economics in the manufacturing industry; however, a comprehensive exploration of its impact on sustainability remains to be explored in detail. Employing a mixed-methods approach and Systems Theory as a theoretical framework, data was gathered from Canon's sustainability reports, financial statements, and online sources, focusing on the years 1997 to 2018. The study analyzes the implementation of digital technologies and their effects on profitability and sustainability outcomes. The research results indicate positive results with sustainable firms able to beat the competition in the long-run, as demonstrated by Canon’s revenue of approximately 36 billion in 2018 alongside significant reductions in CO2 emissions by 435,000 tonnes and a reduction in raw material usage by 314,000 tonnes. Additionally, Canon’s social initiatives, such as the Miraisha Programme, underscore its commitment to inclusivity. This study highlights the multifaceted benefits of integrating digital technologies in manufacturing, offering insights for firms aiming to balance profitability with sustainability.